2018
DOI: 10.30848/pjb2019-2(2)
|View full text |Cite
|
Sign up to set email alerts
|

Influence of boron nutrition on physiological parameters and productivity of cotton (Gossypium hirsutum L.) crop

Abstract: The productivity of arable crops is greatly impacted by imbalanced nutrient management. The deficiency of one or more mineral nutrients can cause substantial reduction in crop yields. Of the micronutrients, the deficiency of boron affects the yield potential of cotton to the greatest extent. This study was carried out to quantify the boron nutritional requirement of cotton. The treatments included three boron levels (0.0, 0.75 and 1.50 kg B ha -1 ) and two application regimes (soil and soil plus foliar). Folia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 20 publications
1
5
0
1
Order By: Relevance
“…1G ). These results are consistent with previous reports showing that B deficiency increased chlorophyll contents in Arabidopsis and cotton [ 53 , 54 ] and suggested a general adaptation mechanism of plants in response to B deficiency.…”
Section: Discussionsupporting
confidence: 93%
“…1G ). These results are consistent with previous reports showing that B deficiency increased chlorophyll contents in Arabidopsis and cotton [ 53 , 54 ] and suggested a general adaptation mechanism of plants in response to B deficiency.…”
Section: Discussionsupporting
confidence: 93%
“…Os nutrientes foliares influenciaram a produção de algodão em caroço, a produção de fibra e o rendimento de fibra (Figura 2; Tabelas 5 e 6), de acordo com várias referências. Os teores de nutrientes foliares são reflexos da fertilidade do solo, que tanto podem aumentar a produção de algodão (Kurt & Temiz, 2016;Shah et al, 2017;Win et al, 2017;Ali et al, 2018;Ahmad et al, 2019;Ali et al, 2020), não alterar a produção de algodão (Silva et al, 2016;Haliloglu, 2019), ou até reduzir a produção de algodão (Seçer et al, 2016;Ajmal et al, 2018).…”
Section: Discussionunclassified
“…The soil B concentration of 0.60 mg•kg −1 extracted with hot water has been considered as the threshold for general crops (Aitken and McCallum 1988) while 0.4∼0.55 mg•kg −1 for cotton (Oosterhuis 2001). Ahmad et al (2019) reported that sandy texture, high pH, and low organic matter content could be the main reasons for low B availability for cotton. Furthermore, high calcium carbonate not only increases the soil pH to reduce B availability but also serves as the binding site for the adsorption of soluble B (Shaaban et al 2004;Shaaban and Helmy 2006).…”
Section: Introductionmentioning
confidence: 99%